Endovascular Treatment of Aneurysm of Splenic Artery Arising from Splenomesentric Trunk Using Stent Graft - Kulkarni, Chinmay Bhimaji (The Korean Society of Radiology, 2013)
We report a rare case of aneurysm of splenic artery arising anomalously from the superior mesenteric artery (SMA). The aneurysm was treated successfully by coil embolization of the splenic artery distal to aneurysm and then deploying a stent graft in the SMA. A combination of stent graft and coil embolization for the treatment of aberrant splenic artery aneurysm has been reported only once. We describe the imaging findings and the endovascular procedure in this patient.